Energetinė šiaurės žemaičių tarmės priegaidžių fonetinės prigimties interpretacija - Girdenis, Aleksas (Baltistica, 1996)
ENERGETIC INTERPRETATION OF PHONETIC NATURE OF TONEMES IN NORTH-ŽEMATIAN DIALECT The acoustic and auditive experiments have shown that the main invariant differential feature of tonemes (syllable accents) of the North-Žemaitian dialect (and, maybe, of Lithuanian in general) is the concentration of the common spectral energy (intensity) and nature of its change. The energy of the acute (sharp, broken) stressed syllables is concentrated in one definite point of a vowel or a diphthong and decreases very sharply; the energy of the circumflexed (smooth, ascending) syllables is diffused in the whole syllable and changes gradually. These processes are accompanied by similar changes of formant structure. In general, the timbre of acute vowels changes abruptly and is more tense than the timbre of corresponding circumflexed vowels.